PHP 8 solutions : dynamic web design and development made easy - Powers, David (Apress, 2022)
Make your websites more dynamic by adding a feedback form, creating a private area where members can upload images that are automatically resized, or storing all your content in a database. David Powers has updated his definitive book to incorporate the latest techniques and changes to PHP with the arrival of PHP 8. New features include named attributes, constructor property promotion, the stricter and more concise match expression, union types, and more.​ The problem is, you're not a programmer and the thought of writing code sends a chill up your spine. Or maybe you've dabbled a bit in PHP and MySQL, but you can't get past baby steps. If this describes you, then you've just found the right book. PHP powers four out of every five websites that use a server-side language. In combination with the MySQL database it's ideal for creating dynamic websites. PHP and MySQL are free, easy to use, and provided by many web hosting companies in their standard packages. This book also covers MariaDB, a seamless replacement for MySQL that has been adopted on many web servers. Unfortunately, most PHP books either expect you to be an expert already or force you to go through endless exercises of little practical value. In contrast, this book gives you real value right away through a series of practical examples that you can incorporate directly into your sites, optimizing performance and adding functionality such as file uploading, email feedback forms, image galleries, content management systems, and much more. Each solution is created with not only functionality in mind, but also visual design. But this book doesn't just provide a collection of ready-made scripts: each PHP solution builds on what's gone before, teaching you the basics of PHP and database design quickly and painlessly. You'll learn how to optimize your code using object-oriented programming (OOP) techniques. By the end of the book, you'll have the confidence to start writing your own scripts or-if you prefer to leave that task to others-to adapt existing scripts to your own requirements. Right from the start, you're shown how easy it is to protect your sites by adopting secure coding practices. What You Will Learn Design and build dynamic PHP-based web sites and applications Get started right away through practical examples that you can reuse Incorporate PHP 8 elements including named attributes, constructor property promotion, and union types.